Etnobotani Jenis Tumbuhan Obat di Kawasan Gunung Inerie, Kabupaten Ngada - Pea, Maria Carina; Semiun, Chatarina Gradict; Pani, Emilianus (Spizaetus: Jurnal Biologi dan Pendidikan Biologi, 2025)
The use of medicinal plants by indigenous communities represents a form of traditional knowledge that serves as a primary alternative for healthcare, especially in areas with limited access to formal medical services. In the Mount Inerie region, Ngada Regency, traditional healing practices are still preserved through the utilization of various local plant species. This study aims to describe the types of medicinal plants used by communities in five villages in Jerebuu District Ngada, Regency as well as to explore the methods of preparation and the cultural values associated with their use. A descriptive method with an ethnobotanical approach was employed, involving semi-structured interviews with 107 respondents, direct observations, and literature studies. The results revealed 33 species of plants used for traditional medicine, with parts such as leaves, rhizomes, fruits, and bark being utilized. Preparation methods include boiling, burning, pounding, or combining with traditional rituals. Knowledge about medicinal plants is passed down orally and remains a primary reference for the community in addressing various health issues. These findings underscore the importance of preserving local knowledge as part of biodiversity conservation and the development of health systems rooted in local wisdom.